1981
DOI: 10.1037/0022-3514.40.5.951
|View full text |Cite
|
Sign up to set email alerts
|

Sources of differential stress response associated with psychometrically designated anxiety proneness.

Abstract: This research examined different aspects of the expression of psychometrically designated anxiety proneness related to dimensions of "ego threat" and "novelty ambiguity." In an ego-threatening situation, subjects were presented with abstract-reasoning items whose stress-relevant properties-item difficulty-had earlier been scaled among comparable samples. In the first study, comparisons focused on objective outcomes (records of task failure) as well as appraised outcome records and appraised task effort necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Analysis of baseline psychophysiological measures indicated that men displayed greater SC levels than women (Ms = 7.40 and 4.93), F(l, 58) = 4.32, p < .05, and that women displayed greater MT levels than men (Ms = 32.87 and 19.87), F(l, 58) = 9.98, p < .01. These observations resemble earlier findings concerning gender differences in the present response modalities (summarized in Dobson & Neufeld, 1981).…”
Section: Pre-experimental Baseline Measuressupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of baseline psychophysiological measures indicated that men displayed greater SC levels than women (Ms = 7.40 and 4.93), F(l, 58) = 4.32, p < .05, and that women displayed greater MT levels than men (Ms = 32.87 and 19.87), F(l, 58) = 9.98, p < .01. These observations resemble earlier findings concerning gender differences in the present response modalities (summarized in Dobson & Neufeld, 1981).…”
Section: Pre-experimental Baseline Measuressupporting
confidence: 92%
“…Again, this "least upper bound" index captured the upper latitude of response during a measurement period. SC, measured this way, has been shown in experimental stress studies to be responsive to aversive stimulus properties (e.g., Dobson & Neufeld, 1981;Lefave & Neufeld, 1980;Mothersill et al, 1986;cf. Neufeld, 1975cf.…”
Section: Methodsmentioning
confidence: 99%
“…This general paradigmatic approach within the present research context has successful precedent in this laboratory, and elsewhere (e.g. Dobson & Neufeld, 1981;Endler, King, Edwards, Kuczynski, Mcguire & Diveky, 1983;Mothersill & Neufeld, 1985). Included in this past work specifically has been the stressor of physical danger/discomfort and vulnerability to its effects (Lefave & Neufeld, 1980;Mothersill, Pobson & Neufeld, 1986).…”
Section: Overviewmentioning
confidence: 85%
“…But this value stems from a somewhat broader perspective involving the relative merits of neurochemical and electrophysiological accounts of personality variables as a "domain of explanation"; the opposing domain consists of somewhat more diffuse cognitive-behavioral accounts. For example, in assessing responses to stressing stimulation among more "anxiety prone" individuals, it has been found that neurosensory formulations surrounding this trait as put forth by Eysenck (1967;1970a) and Gray (1970; appear to be more accurate than those involving "cognitive appraisal of stress" (see Dobson & Neufeld 1981;LeFave & Neufeld 1980;Neufeld & Herzog 1983). A similar assessment may favor the biological-mechanism approach to sensation seeking as espoused by Zuckerman.…”
Section: Department Of Psychology University Of Western Ontario Lonmentioning
confidence: 99%